Pulmonary TB Relapse Case Confirmed Bacteriologically with Cor Pulmonale Chronic Disease - Paramita Yoga, Putu Cahyani (Newinera Publisher, 2025)
Tuberculosis is a chronic infectious disease prevalent in Indonesia caused by Mycobacterium tuberculosis. It primarily affects the lungs but can also invade other organs. It is essential to gather information on the patient's medical history, close contact with TB patients, environmental conditions, and occupation as a healthcare worker to assess the risk of infection transmission. Pulmonary TB can potentially relapse and lead to post-tuberculosis chronic lung disease, which can negatively impact the patient's prognosis and quality of life. If left untreated, it may also result in heart-lung disease, causing disruptions in cardiorespiratory function. Proper treatment is crucial to effectively manage TB and prevent complications.